Tracheostomy decannulation methods and procedures in adults: a systematic scoping review protocol - Kutsukutsa, John (Syst Rev, 2017)
BACKGROUND: The indications for and the number of tracheostomy procedures has increased with advances in critical care. Studies are indicating likely continued increase in number of tracheostomies. Despite the important benefits of a tracheostomy, its presence is associated with adverse health complications and lowered patient quality of life. Hence, it must be decannulated as soon as it is no longer indicated in a safe and effective manner. There is, however, no agreed universal standard of care for tracheostomy decannulation (TD) in adults. The aims of our study are to systematically map the literature on the decannulation process, reveal knowledge gaps and inform further research. METHODS: The search strategy of this systematic scoping review will involve the following electronic databases: PubMed/MEDLINE, Google Scholar, Union Catalogue of Theses and Dissertations (UCTD) via SABINET Online and WorldCat Dissertations and Theses via OCLC. Articles will also be searched through the “Cited by” search as well as citations included in the reference lists of included articles. Studies from the databases will be title screened and duplicates removed followed by a parallel two-independent reviewer screening of abstracts followed by full articles of selected studies both guided by eligibility criteria. We will extract data from the included studies and the emerging themes will be analysed. The relationship of the emerging themes to the research question will be critically examined. The quality of the included studies will be determined by Mixed Method Appraisal Tool (MMAT). We will use NVIVO version 10 to extract the relevant outcomes and thematic analysis of the studies. DISCUSSION: We anticipate to find studies that highlight evidence and preference as well as acceptability of TD methods and procedures. We hope to expose knowledge gaps and inform future research. Findings will be disseminated electronically, in print and through peer presentation, conferences and congresses. SYSTEMATIC REVIEW REGISTRATION: Our systematic review has been registered in PROSPERO: CRD42017072050.